The lipid, fatty acid and fatty alcohol composition of the myctophid fish Electrona antarctica: high level of wax esters and f ood-chain implications - Phleger, C; Nichols, P; Patti Virtue (1997)
The myctophid, Electrona antarctica, was collected by trawl from the Elephant Island region of the Antarctic Peninsula, and from East Antarctica near 61"s and 93"W. Total lipid was higher in Elephant Island E. antarctica (whole fish, 466-585 mg g* dry weight) than those from Eastern Antarctica (394-459 mg g-I). Wax esters comprised 86.2-90.5% of total lipid in E. antarctica flesh. There were no significant differences between Eastern Antarctica and Elephant Island in total wax ester levels, or in levels of wax esters between different tissues analysed. Oily bones (up to 326 mg g1 in the neurocranium) characterized E. antarctica from both locations, with wax esters as the major skeletal lipid class (67.0-87.9%, percent of lipid). The wax esters may have a buoyancy role in E. antarctica. The only substantial amount of triacylglycerols (29.4%) were found in the viscera of Elephant Island fish. The principal fatty acids of all fish analysed included the monounsaturated fatty acids 18:l(n-9) and 16:1(n-7), with lower levels of 16:O and 14:O saturated acids. Fatty alcohols were dominated by the saturated 16:O and 14:O (37.8-47.8%) and the monounsaturated 18:l(n-9) and 18:l(n-7) (38.3-59.2%). The low ratio of 22:1/20:1 alcohols observed for E. antarctica is consistent with a diet of amphipods, copepods and other items low in 22:l alcohols.